The financial burden of knee osteoarthritis patients: a study of healthcare costs and expenses - Rooha Tamimi (Journal of Social & Health Sciences, 2022)
Knee osteoarthritis (OA) is a highly prevalent disease among the elderly population that results in joint degeneration, leading to reduced mobility and challenging daily living. Patients can choose from various treatment options depending on the stage of joint degeneration. In developing countries such as Pakistan, it is crucial to comprehend the financial burden borne by patients and their families due to this condition's high prevalence. Therefore, this exploratory study aimed to assess the financial burden of knee OA patients seeking healthcare services by analyzing the healthcare costs and expenses incurred by them. A purposive sampling technique was employed to recruit 112 knee OA patients undergoing any treatment modality from public and private hospitals in Lahore. A semistructured questionnaire collected patients' sociodemographic information and overall out-of-pocket health expenditures. Descriptive statistics and the Mann‒Whitney U test were utilized for data analysis. The patients' mean age was 53.69 ± 11.73 years, with 10.26 ± 4.83 years of education. Stage III knee OA was the most common diagnosis (30.36%), followed by stage IV (28.57%), stage II (22.32%), and stage I (18.75%). The direct medical cost was significantly higher [United States dollars (USD) 2,590.97] among patients who underwent surgery than among those who opted for alternative treatment procedures (USD 192.10) (p = 0.001). Similarly, the indirect medical cost was significantly higher (USD 371.75) among patients who underwent surgery than among those who chose other treatment options (USD 23.66) (p = 0.001). The overall cost of illness was 6.02 times higher among patients who had surgery (USD 3,050.93) than among those who opted for other treatment modalities (USD 507.19) (p = 0.001). The study’s findings provide insights into the financial burden borne by knee OA patients' families, emphasizing the need for policymakers to intervene. By understanding the costs of illness borne by patients and their families, policymakers can develop targeted interventions to alleviate the financial burden and improve access to healthcare services for knee OA patients.